2004
DOI: 10.1590/s1517-83822004000200011
|View full text |Cite
|
Sign up to set email alerts
|

An optmized protocol for simultaneous extraction of DNA and RNA from soils

Abstract: In this work we report an optimized protocol for simultaneous extraction of DNA and RNA from soil matrices. Treatment of soil matrices with ethanol followed by bead-beating worked as a successful strategy to lyse the cells without considerable degradation of nucleic acids, resulting in DNA and RNA of good yield and integrity. The reverse transcribed RNA could be amplified with primers targeting a glutamine synthetase (glnA) gene fragment. From both DNA and cDNA, 16S rDNA fragments were amplified and analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
(17 reference statements)
0
19
0
1
Order By: Relevance
“…Semiquantitative fluorescence in situ hybridization results for Defluviicoccus-related organisms showed that 4.1% Ϯ 0.6% of the total biovolume hybridizing with the EUBmix probes (5a) also hybridized with the DF1020 probe (12) and that 67.7% Ϯ 3.0% hybridized with the PAOmix probes designed to target "Candidatus Accumulibacter phosphatis" (5,19). Furthermore, comparisons with a range of phenol-based extraction methods (3,4,7,11) with activated-sludge samples showed that our method was equal to or better than these as assessed by PCR targeting the same problematic populations (McIlroy et al, unpublished). Increased safety and a reduced number of pipetting steps make the method suitable for high-throughput analysis.…”
mentioning
confidence: 99%
“…Semiquantitative fluorescence in situ hybridization results for Defluviicoccus-related organisms showed that 4.1% Ϯ 0.6% of the total biovolume hybridizing with the EUBmix probes (5a) also hybridized with the DF1020 probe (12) and that 67.7% Ϯ 3.0% hybridized with the PAOmix probes designed to target "Candidatus Accumulibacter phosphatis" (5,19). Furthermore, comparisons with a range of phenol-based extraction methods (3,4,7,11) with activated-sludge samples showed that our method was equal to or better than these as assessed by PCR targeting the same problematic populations (McIlroy et al, unpublished). Increased safety and a reduced number of pipetting steps make the method suitable for high-throughput analysis.…”
mentioning
confidence: 99%
“…By varying the concentration of template DNA at first PCR level, we have visualized the species, which are unable to detect even at the optimized PCR conditions, particularly the less abundant ones. The optimization of this highly valuable technique of DGGE has been achieved earlier by varying the different parameters as discussed earlier (Wu et al 1998;Hayes et al 1999;Niemi et al 2001;Yu and Morrison, 2004;Costa et al 2004). We have made an attempt in this direction for further improvement, in the application of the technique of PCR-DGGE in the area of microbial diversity analysis with more precision.…”
Section: Dgge Analysismentioning
confidence: 94%
“…The use of denaturing gradient gel electrophoresis (DGGE) to separate mixed PCR products generated from the environmental samples, offers a cultureindependent way for tracking dominant bacterial populations in space and time (Muyzer et al 1993). Optimization of this technique has been performed using different parameters like DGGE primer designing (Wu et al 1998), gel composition and electrophoretic conditions (Hayes et al 1999), comparison of different hypervariable regions for generating fingerprints of microbial communities (Yu and Morrison, 2004), a double or nested PCR approach for improving the sensitivity of detection (Dar et al 2005) and the efficiency of various different methods of DNA extraction and purification from soil samples for improved analysis at community levels (Niemi et al 2001;Costa et al 2004).…”
mentioning
confidence: 99%
“…Electrophoresis of amplification products of the 16S rDNA region of the DNA extracted directly from soil on 1.5% agarose gel. Lanes 1-4: Glass beads method (Costa et al, 2004); Lanes 5-8: Enzymatic method (Hang et al, 2006); Lanes 9-12: Glass beads + PEG8000 method (Yeates et al, 1998) Regarding PCR amplification, the amount of total DNA extracted is less limiting than its quality. Thus, KitCMB protocol offered more promising results, enabling PCR amplification.…”
Section: Choice Of a Protocol For Direct Extraction Of Dna From Soilmentioning
confidence: 99%